1970
DOI: 10.1083/jcb.44.1.172
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Development, and Nature of Intranuclear Rodlets and Associated Bodies in Chicken Sympathetic Neurons

Abstract: Correlative data are presented here on the developmental history, dynamics, histochemistry, and fine structure of intranuclear rodlets in chicken sympathetic neurons from in vivo material and long-term organized tissue cultures . The rodlets consist of bundles of -70 t 10 A proteinaceous filaments closely associated with -0 .4-0 .8 µ spheroidal, granulofibrillar (gf) bodies of a related nature . These bodies are already present in the developing embryo a week or more in advance of the rodlets . In early format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1973
1973
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Cytochemical studies have demonstrated the proteinaceous nature of intranuclear rodlets (Masurovsky et al 1970). Since different cytoskeletal proteins such as actin, tubulin and myosin have been identified as endogenous nuclear proteins (Douvas et al 1975;LeStourgeon et al 1975;Schindler and Jiang 1986), intranuclear rodlets might be formed by local assembly of diffusible forms of such cytoskeletal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochemical studies have demonstrated the proteinaceous nature of intranuclear rodlets (Masurovsky et al 1970). Since different cytoskeletal proteins such as actin, tubulin and myosin have been identified as endogenous nuclear proteins (Douvas et al 1975;LeStourgeon et al 1975;Schindler and Jiang 1986), intranuclear rodlets might be formed by local assembly of diffusible forms of such cytoskeletal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, nuclear inclusions (NIs) other than nuclear bodies have not been sufficiently reported except for neural tissues (Masurovsky et al 1970;Vazquez et al 1970;Tani 1971;Shaw and Sumi 1975) and endocrine organs (Boquist 1969;Dahl 1970;Sherwin et al 1977; Ryder et al 1979; DeLellis et al 1980). Through a systematic observation of several polypoid lesions and carcinomas of the large bowel, we found a number of nuclear inclusions.…”
mentioning
confidence: 66%
“…Figure 9 shows an electron micrograph of a neutrophil leukocyte treated with 0.5% pepsin for 30min the intranuclear inclusions remained undisturbed. HIRANO and ZIMMERMAN, 1967;POPOFF and STEWART, 1968;MASUROVSKY et al, 1970) noted the filamentous structure in similar nuclear inclusions in neurons. Cell Tiss.…”
Section: Frequencymentioning
confidence: 99%
“…According to these authors, there are three types of intranuclear inclusions which differ in ultrastructure from each other: filamentous (MASUROVSKY et al, 1970;WARCHOL, 1978;SEITE et al, 1979), microtubular (SEITE et al, 1979) and crystalline (CHANDLER and WILLIS, 1966;PATRIZI and MIDDELKAMP, 1969;LAFARGA and PALACIOS, 1979 (MAGALHAES, 1967), the dog epididymidis (GOURANTON et al, 1979), the rat pineal (BOQUIST, 1969 …”
mentioning
confidence: 99%
See 1 more Smart Citation